Implementasi Informasi Mengenai Covid-19 Pada Web Iklan Berbasis Mobile - Nafida Tohiroh (SOTVI - Society of Visual Informatics, 2021)
Information is data that has been processed so that it has a certain value or meaning. This valid information is important so that people understand and know more about news or new knowledge. One of the latest news today is the Covid-19 pandemic whose spread still cannot be stopped. Among the many hoaxes that haunt the public, it is necessary to have a reliable source that provides the latest information about COVID-19 in Indonesia. One of the efforts to prevent this hoax is by disseminating information about covid through advertisement-based web. Ads that are based on data and accompanied by a valid data source will be a trusted source of information. In addition, the existence of an ad design that is easy to understand and clear will make the web ad more acceptable in the community. This mobile-based web advertisement is published through social media so that it will be more accessible to the public.